2017
DOI: 10.1088/1361-6498/aa80f5
|View full text |Cite
|
Sign up to set email alerts
|

Collateral contamination concomitant to the polonium-210 poisoning of Mr Alexander Litvinenko

Abstract: Mr Litvinenko died on 23 November 2006, having been poisoned with polonium-210 on 1 November, with evidence of a previous poisoning attempt during October 2006. Measurements of Po in urine samples were made for a large number of people to determine whether they may have been contaminated. In the majority of cases, measured levels were attributable to the presence ofPo from normal dietary sources. For a small number of cases, elevated levels provided evidence of direct contamination associated with the poisonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…At the time of the poisoning of Alexander Litvinenko in 2006, an upper value on urinary excretion of naturally occurring 210 Po was required to allow the identification of individuals exposed as a result of the incident (Bailey et al 2008, 2010, Harrison et al 2017. A rapid review of the literature indicated that average daily excretion of 210 Po was typically of the order of 5 and 10 mBq d −1 , for non-smokers and smokers, respectively, and suggested that values above 30 mBq d −1 were unlikely to be solely due to a 'natural' intake of 210 Po.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of the poisoning of Alexander Litvinenko in 2006, an upper value on urinary excretion of naturally occurring 210 Po was required to allow the identification of individuals exposed as a result of the incident (Bailey et al 2008, 2010, Harrison et al 2017. A rapid review of the literature indicated that average daily excretion of 210 Po was typically of the order of 5 and 10 mBq d −1 , for non-smokers and smokers, respectively, and suggested that values above 30 mBq d −1 were unlikely to be solely due to a 'natural' intake of 210 Po.…”
Section: Discussionmentioning
confidence: 99%
“…Variability in excretion rates will also result from differences between individuals in the biokinetics and organ retention of 210 Po (ICRP 1993, Leggett andEckerman 2001). Harrison et al (2017) discussed the interpretation of measurements of 210 Po in urine samples provided by a large number of people at the time of the poisoning of Mr Alexander Litvinenko in London in November 2006. Interpretation of urine measurements to assess the probability of contamination from artificial sources must take into account natural levels and their variability.…”
Section: Introductionmentioning
confidence: 99%
“…A Russian publication reports at least four criminal actions involving gamma sources (Krasniouk 2004, Nénot 2009. More recently, Po-210 was used in the poisoning of Mr Alexander Litvinenko (Harrison et al 2017a), which led also to collateral contamination of other individuals, including eight that received effective doses in the range of 10-100 mSv (Harrison et al 2017b).…”
Section: Malicious Activitiesmentioning
confidence: 99%
“…Due to the poisoning of Mr Litvinenko, many other people became contaminated with 210 Po, albeit at much lower levels. This was explored in a study by Harrison et al (2017b), who analysed over 800 24 h urine samples taken from people judged to be at risk of contamination. A total of 819 measurements were taken to correspond to natural background levels.…”
mentioning
confidence: 99%
“…Substantially higher effective doses in the range of a few hundred mSv to a few Sv were estimated for two individuals, for whom data were provided to the Litvinenko Inquiry by an Expert Commission in the Russian Federation. Harrison et al (2017b) relate these estimated doses from 210 Po to risks of health effects, from the certainty of death at high doses to inferred risks of cancer at low doses. Overall, this study demonstrates the substantial effort needed to monitor potentially exposed individuals following accidental or deliberate releases of radionuclides to the environment.…”
mentioning
confidence: 99%